Pengembangan Sistem Manajemen Event Pameran Karya Mahasiswa Menggunakan Metode Extreme Programming - Ahmad Ali Mutezar; Umniy Salamah (Ikatan Ahli Informatika Indonesia (IAII), 2021)
An event is a means for students to improve their soft skill and hard skill. In college, one kind of event that usually held regularly is an exhibition. It is usually held around the universities environtment, but in practice there are still some shortcomings, such as the registration process is done manually, attendance of participants that are not integrated with the system, and unavailability of certificates for participants who have attended the event. Since the outbreak of Covid-19, organizing the events must be done online, so we need a system that can accommodate this. Therefore, this study aims to create an event management system that can manage exhibition event data. Besides, the system is also equipped with a feature to generate an E-Certificate that has a QR Code embedded. The method used in this study is Extreme Programming, with its flexible nature toward changes to facilitate the process of system development. The testing in this study is using black box method, with the test results show that all functional in the system can run well in accordance with user expectations. The use of the Extreme Programming method produces a quality system, because users are involved during the system development process.